Harvesting Energy from fat-tail random vibrations - Peña Rosselló, Julián Ignacio (2015)
We illustrate how applied and computational mathematics tools in the field of probability, statistics and stochastic processes are applied in the preliminary design stage of an expectedly typical 21th century (nanotech) industrial process: the fabrication of carpets, paints and networks able to harvest energy from random vibrations.